2009
DOI: 10.1002/adsc.200900501
|View full text |Cite
|
Sign up to set email alerts
|

Palladium on Charcoal as a Recyclable Catalyst for CS Cross‐Coupling of Thiols with Aryl Halides under Ligand‐Free Conditions

Abstract: S-Arylation of a wide variety of substituted aryl and aliphatic thiols with aryl halides using a catalytic amount of palladium on charcoal as a heterogeneous catalysis with potassium hydroxide as the base in dimethyl sulfoxide (DMSO) at 110 8C is accomplished in good yields. The C À S bond formation reaction functions under ligand-free conditions, and the palladium on charcoal catalyst can be is reused for five runs without any loss of activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…The method provides biaryl sulfides in good yields, but is limited to aryl bromides and also requires high reaction temperatures and long reaction times (Equation 1). Typically, the palladium-catalyzed methods following Migita’s report utilize catalysts containing bidentate phosphine ligands [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The bidentate phosphine-ligated systems are proposed to be successful because of their ability to stay coordinated to the metal upon attack of the thiolates at palladium.…”
Section: Palladium-catalyzed Arylation Of Thiolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method provides biaryl sulfides in good yields, but is limited to aryl bromides and also requires high reaction temperatures and long reaction times (Equation 1). Typically, the palladium-catalyzed methods following Migita’s report utilize catalysts containing bidentate phosphine ligands [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The bidentate phosphine-ligated systems are proposed to be successful because of their ability to stay coordinated to the metal upon attack of the thiolates at palladium.…”
Section: Palladium-catalyzed Arylation Of Thiolsmentioning
confidence: 99%
“…Lin and co-workers recently reported the first Pd/C catalyzed arylation of thiols [ 53 ]. This ligand-free process is limited to the use of aryl iodides and activated aryl bromides.…”
Section: Palladium-catalyzed Arylation Of Thiolsmentioning
confidence: 99%
“…Lin's group reported recyclable Pd/C as the catalyst for the C–S cross‐coupling reaction of a wide variety of substituted aromatic and aliphatic thiols with aryl halides without ligand in the presence of potassium hydroxide in DMSO [Eq. (30)] …”
Section: Applications Of Pd/cmentioning
confidence: 99%
“…In 2009, Jiang et al [56] reported a similar process using Pd on charcoal under ligand-free conditions. The reaction was performed at 110 ∘ C in dimethyl sulfoxide (DMSO) for 9 h using 2 mol% Pd, and excellent yields were obtained.…”
Section: Migita Thioether Synthesis (C Ar -Sr Bond Formation)mentioning
confidence: 99%